4Ever Fit Gym and Fitness / Muhammad Farid Wajdi Naksahbandi ... [et al.] - Naksahbandi, Muhammad Farid Wajdi; Mohamad Fizi, Anas Azfar; Maula Hussin, Mohammad Razali; Zainal, Ahmad Nuraizat; Elias, Elisa Natasha; Ayob, Aira Syazwina; Haripin, Nuraida Shada (2015)
Administration plan bring the means of the management of our company regarding the management of internal affairs of the business. Administration plan will lead to a better systematic flow of operation within the organization and aims to achieve a good quality of services to customers. Our company which is 4Ever Fit Gym and Fitness is managed by 7 managers which are lead by the General Manager. The respective managers are Muhammad Farid Wajdi bin Naksahbandi (General Manager), Anas Azfar bin Mohamad Fizi (Marketing Manager 1), Ahmad Nuraizat bin Zainal (Marketing Manager 2), Mohamad Razali bin Maula Hussin (Operating Manager), Elisa Natasha binti Elias (Administration Manager), Aira Syazwina binti Ayob (Financial Manager 1), and Nuraida Shadah binti Haripin (Financial Manager 2).